Antioxidant Activity Analysis of Endophytic Fungal Isolates IFBZ5, IFBZ6, and IFBZ7 from the Stem of Bidara (Ziziphus mauritiana Lam.) - Fitriana, Fitriana; Tahir, Masdiana; Hamdhan, Aulia Nurul Insani; Sumardi, Farah Hikmah Nur; Putri, Adinda (Journal Microbiology Science, 2025)
Endophytic fungal isolates coded IFBZ5, IFBZ6, and IFBZ7 derived from the stem of the bidara plant (Ziziphus mauritiana Lam.) have shown potential antioxidant properties. This study aims to test the antioxidant activity of endophytic fungal isolates on the bidara plant stem (Ziziphus mauritiana Lam.) by TLC-Autography method and DPPH (1,1-diphenyl-2-picrylhydrazil) free radical silencing. This study used endophytic fungi isolates code IFBZ-5, IFBZ-6 and IFBZ-7 which were fermented for 21 days using MYB medium which was then liquid-liquid extracted with ethyl acetate (1:1) and evaporated. The fermentate extract obtained was then tested for antioxidant activity qualitatively and quantitatively. Qualitative analysis using TLC plates indicated antioxidant activity in all isolates. Quantitative analysis showed that isolate IFBZ7 exhibited strong antioxidant activity with an IC50 value of 50.120 ppm, while IFBZ5 and IFBZ6 showed very weak activity with IC50 values of 2.482.363 µg/mL and 467.847 µg/mL, respectively. The BHT comparator had an IC50 value of 6.778 µg/mL. This shows that the antioxidant power of endophytic fungal isolates coded IFBZ5, IFBZ6 and IFBZ7 is lower than the antioxidant activity of BHT as a comparison.